Legal Aspects of Refunding Excess Tax Payments to Consumers - Azwir Agus (Civiliza Publishing, 2026)
Consumption tax plays a strategic role as a source of state revenue that supports development financing and the implementation of government functions. In its implementation, there is a possibility of tax payments exceeding the amount due due to administrative errors, miscalculations, changes or cancellations of transactions, and corrections to the tax base. Legal issues arise when consumers, as the parties who economically bear the tax burden, do not have a transparent, easily accessible, and certain refund mechanism. This study aims to examine the regulations and mechanisms for refunding excess tax payments to consumers from the perspective of legal certainty and fiscal justice. This study uses a normative legal research method with a statutory and conceptual approach. The results show that the refund mechanism tends to focus on those who are formally recognized as taxpayers or those who make payments. This situation has the potential to create an imbalance between the formal recipients of refunds and those who actually bear the tax burden. Therefore, strengthening verification mechanisms, transparency, and proportional refunds is necessary to protect consumer rights and achieve fiscal justice.